Amides do not always work: observation of guest binding in an amide-functionalised porous host - Benson, Oguarabau; Da Silva, Ivan; Argent, Stephen P.; Cabot, Rafel; Savage, Mathew; Godfrey, Harry G.W.; Yan, Yong; Parker, Stewart F.; Manuel, Pascal; Lennox, Matthew J.; Mitra, Tamoghna; Easun, Timothy L.; et al. (American Chemical Society, 2016)
An amide-functionalised metal organic frame-work (MOF) material, MFM-136, shows a high CO2 uptake of 12.6 mmol g-1 at 20 bar and 298 K. MFM-136 is the first example of acylamide pyrimidyl isophthalate MOF without open metal sites, and thus provides a unique platform to study guest bind-ing, particularly the role of free amides. Neutron diffraction reveals that, surprisingly, there is no direct binding between the adsorbed CO2/CH4 molecules and the pendant amide group in the pore. This observation has been confirmed un-ambiguously by inelastic neutron spectroscopy. This suggests that introduction of functional groups solely may not neces-sarily induce specific guest-host binding in porous materials, but it is a combination of pore size, geometry, and functional group that leads to enhanced gas adsorption properties.